FIGURE 12 in Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata) - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
FIGURE 12. Rhamphostomella bilaminata (Hincks, 1877). A, E, F. ZIRAS 23/50121 (western Kamchatka, Sea of Okhotsk). B–D, G–I. NHMUK 1911.10.1.1579A (Gulf of St Lawrence, Atlantic Ocean). J–L. ZIRAS 24/50122 (Avacha Gulf, eastern Kamchatka, Pacific Ocean). A. Colony margin with developing zooids and ooecia. B. Distal view of ovicellate zooids, showing proximal margin of primary orifice with lyrula and denticles. C. Suboral avicularium. D. Non-ovicellate zooids with additional calcified layer expanding over frontal shield. E. Zooids with developing ooecia. F. Zooids with developing and one completed ooecia. G. Group of ovicellate zooids in older part of colony. H. Suboral avicularium in ovicellate zooid. I. Interior of frontal shield, showing umbonuloid component and ooecial communication pore (arrow). J. Basal surface of colony. K. Interior of frontal shield, showing ring scar and umbonuloid component, and median lyrula and two sinuses. L. Lateral view of zooid with a peristome, suboral avicularium, and ooecium; zooidal lateral wall shows mural pore chambers. Scale bars: A, D, G, 250 μm; B, E, F, H, I, 100 μm; C, K, 50 μm; J, 500 μm; L, 200 μm. Published as part of Grischenko, Andrei V., Gordon, Dennis P., Taylor, Paul D., Kuklinski, Piotr, Denisenko, Nina V., Spencer-Jones, Mary E. & Ostrovsky, Andrew N., 2022, Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata), pp. 1-115 in Zootaxa 5131 (1) on page 44, DOI:10.11646/zootaxa.5131.1.1, http://zenodo.org/record/6521113